The Kingdom of God in the philosophy of Sergius Hessen - Mikhail Zagirnyak (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия)
The concept of the “Kingdom of God” appears in the philosophy of Sergey (Sergius) Iosifovitch Hessen (1887–1950) in the late period of his work, in 1928, and in the mid-1930s became the most important element in his doctrine of the four planes of being. Paying attention to certain aspects of this doctrine, researchers of Hessen's philosophy have not studied its place in the philosophy of the thinker. Meanwhile, it is the determination of the place of this doctrine that makes it possible to assess the significance of the concept of the Kingdom of God for Hessen. In the given study, the analysis of the doctrine of the four planes of being allows us to consider it as an organic component of Hessen's philosophy. The research hypothesis is that the doctrine of the four planes of being embraced the most important ideas of Hessen, formed during his creative life, into a generalized philosophical system that offers an answer to the questions about the meaning of human life and the meaning of human history. The Kingdom of God in Hessen's philosophical system is the most important concept that allows him to link pedagogical, socio-philosophical, and legal ideas in a unified view of the sociocultural process without contradictions. To confirm the research theses, the most important ideas of Hessen, formed before the actualization of the concept of the Kingdom of God in his own philosophy, are considered, his conceptual apparatus is analyzed to show how Hessen, without abandoning them, adds to them the concept of the Kingdom of God. In Hessen's philosophy, the Kingdom of God is a transcendent ideal, which is fundamentally unrealizable in the earthly temporal existence of mankind. It allows Hessen to combine in his own doctrine the freedom of man with the definition of the goal of the historical development of society, avoiding sociological nominalism and universalism. Hessen's philosophical path, viewed through the prism of the doctrine of the four planes of being, represents a systematic deepening of views in the substantiation of the sociocultural process. This article allows us to understand Hessen's final philosophical intent, his final justification of the meaning of human history.